Bone Mineral Density of Adolescent Female Tennis Players and Nontennis Players - Kevser Ermin; Scott Owens; M. Allison Ford; Martha Bass (Journal of Osteoporosis)
The purpose of this study was to determine differences in bone mineral density (BMD) among adolescent female tennis players (TPs) and nontennis players (NTPs) and to assess body composition as a predictor variable of BMD. Nineteen female TPs and 19 female NTPs, ages 14 to 18 years, participated in this study. Lumbar spine, total hip, femoral neck, forearms BMD, and body composition were assessed using dual-energy X-ray absorptiometry (DXA). Lumbar spine and total hip BMD measurements for TP were greater than NTP. However, these differences were not statistically significant (𝑃=0.37 and 0.12, resp.). TP had significantly greater femoral neck BMD than NTPs (𝑃=0.02). This difference might play an important role in preventing osteoporosis and decreasing the risk of fractures at the hip later in life.